Gender difference in self-reported empathy: Effects of task instructions and exposure to gender essentialism primes - Namitha Rajasekhar; Anna Redly; Shevantika Nanda; Gillian R. Brown (PLoS ONE, 2025)
Women often score higher on average than men on self-report measures of empathy. However, self-report estimates of empathic tendencies and other attributes could be susceptible to a range of biases. For instance, participants might respond in a manner that is socially desirable and aligns with gender stereotypes about empathic abilities. We examined whether gender differences in self-reported empathy were affected by a) manipulating task instructions or b) priming with fictive narratives describing gender differences as either fixed or malleable. In Study 1, participants (N = 154) completed questionnaire measures of empathy, social desirability and acceptance of stereotyping. Contrary to our prediction, gender differences in self-reported empathy were not larger when participants were told that we were measuring ‘empathy’. However, in both genders, average scores were higher for empathic concern in the ‘empathy’ condition than in the control condition, which suggests that describing the task as measuring empathy encouraged both male and female participants to present themselves as showing concern for others. Also, participants who scored higher on social desirability scored higher on empathic concern, suggesting a link between motivation to conform to social expectations and self-reported affective empathy. In Study 2, participants (N = 155) completed questionnaire measures of empathy, personality and gender essentialism. Gender differences in self-reported empathy were not larger in the condition that primed gender essentialism. However, women who scored high on empathic concern were more likely to align themselves with feminine adjectives, suggesting a link between self-reported consideration for others and feminine attributes. In both studies, on average, women scored significantly higher than men on self-reported empathic tendencies. Although the experimental manipulations did not impact empathy scores in either study, self-reported empathy appears to be related to social desirability and broader social attitudes, which suggests that a range of cultural and social factors might contribute to gender differences in empathy.